Integrating Flipped Learning Approach to Foster Students Self-Directed Learning in Science Learning - Hendra Setiawan; Achmad Ramadhan; Merry Kristhiani (CV. Dharma Samakta Edukhatulistiwa, 2025)
This study aims to describe the integration of the Flipped Learning approach in fostering students’ learning autonomy in Grade XI Biology at SMA Negeri 2 Palu, particularly on the topic of the Human Reproductive System. The research subjects consisted of 35 students. The study was conducted as Classroom Action Research (CAR) over two cycles, each comprising two meetings. Data were collected through teacher and student activity observations, formative tests, and student reflections, and analyzed using both quantitative descriptive and qualitative methods. The findings reveal that the percentage of teacher activity increased from 70% and 75% in cycle I to 85% and 95% in cycle II, while student activity increased from 50% in both meetings of cycle I to 72.5% and 85% in cycle II. Students’ average formative test scores also improved from 58.1% and 62.7% in cycle I to 76.3% and 83.9% in cycle II. Student reflections indicated enhanced motivation, active participation, and readiness for independent learning. These findings suggest that science learning through the Flipped Learning approach can foster students’ learning autonomy while simultaneously facilitating critical thinking skills and the effective use of technology required to meet the challenges of 21st-century education.